Peningkatan Hasil Belajar Operasi Hitung Campuran melalui Media Seblak Matematika pada Siswa Kelas III SDN Bakalan Sumobito - Mochammad Syafiuddin Shobirin; Rohmat Hidayat; Iin Baroroh Ma’arif; Luluk Choirun Nisak; Nabil Yahsa Hubaib; Rafiqa Rahmayati; Rifda Nabila Azzadi; Mery Ristanti; Neny Liftia (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2025)
This study aims to enhance students’ achievement in solving mixed arithmetic operations through the implementation of Seblak Mathematics media for third-grade students at SDN Bakalan Sumobito. The research was motivated by the low level of student interest and engagement in mathematics learning, which has largely been dominated by conventional methods and abstract explanations. Seblak Mathematics was developed as a contextual learning medium by integrating seblak, a local culinary element, to create lessons that are both engaging and closely tied to students’ everyday experiences. The research employed several stages, including needs analysis, media design, classroom implementation, and evaluation through teacher reflection. Findings revealed that the use of Seblak Mathematics significantly improved students’ learning motivation, strengthened classroom interactions, and deepened their understanding of mixed arithmetic concepts. Teachers responded positively, highlighting the practicality, ease of application, and adaptability of the media across various classroom conditions. In conclusion, this study demonstrates that culturally relevant and creative learning media can substantially improve elementary students’ mathematics performance. Furthermore, such media fosters active participation, enjoyable learning, and more meaningful classroom experiences.